GEOPOLITICAL AND ECONOMIC INTERESTS OF THE RUSSIAN EMPIRE IN THE SECOND HALF OF THE 19th CENTURY IN CENTRAL ASIA - Chinpulat Minasidinovich Kurbanov, Sharif Safarovich Shaniyazov, Jaloliddin Bakhromovich Nurfayziev, Mukhriddin Azimmurod-ugli Sherboboev, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In this scientific article, the author examines such issues as Russian industry entered the capitalist path of development, how the importance of Central Asia as a sales market has grown many times. In addition, what a huge intermediary role Central Asia played in the transit of Russian goods to Afghanistan, Iran, India and China. The problems of conquering through the accession and development of new Central Asian markets of the second half of the 19th century became the primary task of the foreign policy of the Russian Empire. The development of new markets led to the gradual blurring of the borders between domestic and foreign markets, which, in turn, contributed to the pulling of many countries into the world market.